Libertà religiosa e terapie di conversione sessuale: itinerari ricostruttivi nel diritto sovranazionale e comparato - Ferrari, Daniele (Il diritto ecclesiastico, 2023)
Freedom of Religion and sexual conversion therapies. Reconstructive paths in supranational and comparative law · This paper provides a legal investigation of the category ‘religious conversion therapy’ under international and comparative law in US. The goal is to clarify the relationship between ‘freedom of religion’ and ‘freedom of sexual orientation’ by analysing legal documents and cases law. The evolutionary trajectory of this relationship is then explained moving from the historical condemnation of homosexual acts by religion to the ambivalence of freedom of religion in the sphere of sexual (re)orientation in human rights system.